COOPERATIVE REGIONAL DEVELOPMENT: A SOCIOECONOMIC CHARACTERIZATION OF COOPERATIVE SHEEP BREEDER THE MUNICIPALITY OF SANTIAGO/RS - Guse, Jaqueline Carla; Dörr, Andréa Cristina; Rossato, Marivane Vestena; Freitas, Luiz Antônio Rossi de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708730 The cooperatives and associations are the alternative ways to work together in order to achieve good financial results and organizational for all individuals involved. The Sheep Cooperative Santiago (Cooperovinos) emerged with the aim of achieving the best markets for the marketing of sheep production in the municipality of Santiago. Thus, this work studies the socioeconomic situation of the Sheep Cooperative in the municipality of Santiago from the perspective of the benefits for the producers involved. The methodology used in this research is the application of case study. The results show that Cooperovinos works with the aim of shortening distances between producer and market, bringing higher returns to producers involved. We conclude that the main benefit generated to sheep producers are paying a higher price for products to market, access to marketing channels more sophisticated and adding value to the product.